Comparative study of stability and transport of molecules through cyclic peptide nanotube and aquaporin: a molecular dynamics simulation approach. Issue 1 (2nd January 2020) - Maroli, Nikhil; Kolandaivel, Ponmalai
Abstract: The structural stability and transport properties of the cyclic peptide nanotube (CPN) 8 × [Cys–Gly–Met–Gly]2 in different phospholipid bilayers such as POPA (1-palmitoyl-2-oleoyl-sn-glycero-3-phosphatidic acid), POPE (1-palmitoyl-2-oleoyl-sn-glycero-3-phosphoethanolamine), POPC (1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine), POPG (1-palmitoyl-2-oleoyl-sn-glycero-3-phosphoglycerol) and POPS (1-palmitoyl-2-oleoyl-sn-glycero-3-phosphoserine) with water have been investigated using molecular dynamics (MD) simulation. The hydrogen bonds and non-bonded interaction energies were calculated to study the stability in different bilayers. One µs MD simulation in POPA lipid membrane reveals the stability of the cyclic peptide nanotube, and the simulations at various temperatures manifest the higher stability of 8 × [Cys–Gly–Met–Gly]2 . We demonstrated that the presence of sulphur-containing amino acids in CPN enhances the stability through disulphide bonds between the adjacent rings. Further, the water permeation coefficient of the CPN is calculated and compared with human aquaporin-2 (AQP2) channel protein. It is found that the coefficients are highly comparable to the AQP2 channel though the mechanism of water transport is not similar to AQP 2; the flow of water in the CPN is taking place as a two-line 1–2–1–2 file fashion. In addition to that, the transport behavior of Na + and K + ions, single water molecule, urea and anti-cancer drug fluorouracil were investigated using pulling simulation and potential of mean force calculation. The above transport behavior shows that Na + is trapped in CPN for a longer time than other molecules. Also, the interactions of the ions and molecules in Cα and mid-Cα plane were studied to understand the transport behavior of the CPN. Abbreviations: AQP2 Aquaporin-2 CPN Cyclic peptide nanotube MD Molecular dynamics POPA 1-Palmitoyl-2-oleoyl-sn-glycero-3-phosphatidic acid POPE 1-Palmitoyl-2-oleoyl-sn-glycero-3-phosphoethanolamine POPG 1-Palmitoyl-2-oleoyl-sn-glycero-3-phosphoglycerol POPS 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphoserine Communicated by Ramaswamy H. Sarma